Analisis Pengaruh Investasi PMA dan Nilai Tukar terhadap Nilai Ekspor serta Dampaknya terhadap Perekonomian Indonesia - Asrini, Asrini; Devita, Andri; Rosita, Ratih; Fitri, Risma (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of PMA investment and exchange rates simultaneously and partially on the value of exports in Indonesia, as well as the effect of export values on economic growth during the period 2010-2023. The results of the study indicate that PMA investment has a positive and significant effect on the value of Indonesian exports. However, it is inversely proportional to the IDR/USD exchange rate which has a negative and insignificant effect on the value of Indonesian exports during the period 2010-2023. In addition, the export value has a positive and significant effect on the Indonesian economy during the period 2010-2023.